Pengembangan bahan ajar berupa e-book pada mata pelajaran akuntansi keuangan kompetensi dasar akuntansi piutang kelas XI berbasis pendekatan saintifik di SMK Yapalis Krian - Sylvia Maulidah Rahmah; Joni Susilowibowo (Jurnal Riset Pendidikan Ekonomi, 2021)
This research aims to develop e-book teaching materials, analyze the feasibility level of e-books and analyze student responses to e-books. The subjects in this study are financial accounting on the basic competence of accounts receivable accounting. Teaching materials in the form of e-books were developed according to the implementation of the 2013 curriculum based on a scientific approach. The research method used is Research and Development (R&D) with a 4-D model. The validators in the study were 3 lecturers according to the intended field and one teacher who was an expert in financial accounting subjects. The assessment data distributed to the validator comes from the review sheet and then the validation sheet. A total of 20 students of class XI Financial and Institutional Accounting at SMK Yapalis Krian were also one of the respondents. This is to determine the feasibility of teaching materials so that they are suitable for use in the learning process. The product developed produces a very feasible interpretation with an average feasibility recapitulation of 89.49%. From these results, there are several components listed with very feasible interpretations, namely the feasibility of the material 89.89%, the feasibility of language 86.67% and the feasibility of graphics 91.93%. For the average results, students stated that the interpretation was very well understood with a percentage of 88.12%. So this teaching material is suitable for use in the learning process